PSYCHOLOGICAL CONTRACT VIOLATION AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Othman, Rozhan; Arshad, Rasidah; Hashim, Noor Azuan; Isa, Rosmah Md (Gadjah Mada International Journal of Business, 2005)
A psychological contract is an implicit understanding between a group of employees and their employer that arose as a result of a particular leadership style. Psychological contract violation (PCV) is said to occur when there is a perceived breach of promise that leads to an emotional and affective response. The literature on PCV posits a number of antecedents and outcomes of PCV. This study seeks to develop a model of PCV by linking it with justice and organizational citizenship behavior (OCB). It is argued that the antecedents of PCV lead to a sense of injustice. These will then create the emotional response that is indicative of PCV. It is also argued that an outcome of this PCV experience is reduced OCB and the emergence of a new outlook towards employment relationship. Data was collected from a Malaysian company that initiated a voluntary separation scheme as part of an effort to downsize its work force. The finding of this study provides partial support for the model.